Behaviorist-Cognitivist Integration in Arabic Writing Instruction: An Empirical Study at Surabaya Islamic Junior High School - Mubarok, Ahmad Shofiyyul; Yusuf , Kamal; Fikri , Abdul Hakim Ali (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
Low proficiency in Arabic writing among students continues to pose a significant educational challenge, primarily due to conventional teaching methods that lack integration of robust learning theories. This study examines the impact of combining behaviorist and cognitivist approaches to enhance Arabic writing skills among eighth-grade students at MTs Alif Laam Miim Surabaya. Utilizing a mixed-methods case study design, 30 students were purposively selected as participants. Data were gathered through observations, interviews, writing assessments, and questionnaires. Quantitative results using paired-sample t-tests indicated a statistically significant improvement in writing scores, with an average gain of 19.00 points (p < 0.001; Cohen’s d = 2.44). Qualitative findings revealed increased motivation, confidence, and reflective writing habits, including planning and self-evaluation. The study highlights that blending behaviorist drills with cognitively engaging strategies creates a more dynamic and student-centered learning atmosphere. The novelty of the research lies in demonstrating that integrating these theories not only enhances linguistic accuracy but also fosters metacognitive growth and writing creativity. This contributes valuable insights for curriculum development and teacher training. The proposed model offers a balanced, empirically grounded approach to Arabic writing instruction. Further studies are recommended to incorporate digital tools or explore constructivist methods and evaluate their long-term effectiveness.